Treatment of multiple adjacent gingival recession - Shan-Huey Yu; Harlan J. Shiau (Elsevier, 2024)
Gingival recession is a prevalent mucogingival deformity and condition associated with teeth, often occurring in patterns involving multiple adjacent sites. This presentation by the patient is frequently framed as an aesthetic concern, because of the imbalance in white and pink esthetic proportions, or related to a complaint of dentin hypersensitivity. The clinician is required to understand the etiologic factors specific to this recession pattern. Modification or management of these factors contributing to multiple adjacent gingival recession should be included as part of the overall treatment plan to increase efficacy of surgical root coverage procedures. The current treatment options for multiple gingival recession include tunneling and coronally advanced flap techniques with varying technical modifications. The aim of this narrative review is to explore the development of these procedures utilized to manage patients presenting with multiple adjacent gingival recession.